Ouabain alleviates Mycobacterium abscessus-triggered inflammatory responses through dual regulation of NLRP3 inflammasome activity and M1 macrophage polarization - Li, Nan; Huang, Songqiang; Shi, Xing; Lu, Kuo; Yu, Xiu; Qiu, Chen; Chen, Rongchang (Frontiers in Immunology, 2025)
IntroductionMycobacterium abscessus (M. abscessus) is a highly drug-resistant pathogen responsible for chronic pulmonary inflammation in humans. The cardiac glycoside ouabain exhibits broad anti-inflammatory effects in various disease models, but its therapeutic potential against M. abscessus-induced pneumonia remains unexplored.MethodsWe investigated the role of ouabain in M. abscessus-induced inflammation using in vivo and in vitro models. Inflammatory responses were assessed through cytokine expression analysis (TNF-α, IL-6, IL-1β), histopathological examination (H&E staining), transcriptomic profiling, IHC, TEM and qPCR. The effects of ouabain on NLRP3 inflammasome activation and macrophage polarization were also evaluated.ResultsOuabain significantly reduced M. abscessus-induced inflammation by suppressing proinflammatory cytokines (TNF-α, IL-6, IL-1β) and attenuating lung tissue damage. Transcriptomic and qPCR analyses confirmed that ouabain downregulated NLRP3 inflammasome activity and IL-1β secretion in vivo. In vitro studies further demonstrated that ouabain inhibited NLRP3 inflammasome activation and M1 macrophage polarization.DiscussionThese findings indicate that ouabain mitigates M. abscessus-induced pulmonary inflammation through dual mechanisms: suppression of NLRP3 inflammasome activation and modulation of M1 macrophage polarization. This study highlights ouabain’s potential as a therapeutic candidate for M. abscessus infections.